New record of the non-indigenous crab Percnon gibbesi (H. Milne Edwards, 1853) from Palagruža archipelago (Adriatic Sea) - Dulčić, Jakov (Array, 2019)
Several individuals of non-indigenous grapsid crab Percnon gibbesi (H. Milne Edwards, 1853) have been observed and photographed in the area of Palagruža archipelago (Adriatic Sea, Croatia). This is additional confirmed record of this species in the Adriatic Sea. It suggests subsequent range expansion of this species and provides further evidence of its establishment in Adriatic waters.